2016
DOI: 10.1021/acs.biomac.5b01543
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in Vitro Mineralization and in Vivo Osteogenesis of Composite Scaffolds through Controlled Surface Grafting of l-Lactic Acid Oligomer on Nanohydroxyapatite

Abstract: Nanocomposite of hydroxyapatite (HA) surface grafted with L-lactic acid oligomer (LAc oligomer) (op-HA) showed improved interface compatibility, mechanical property, and biocompatibility in our previous study. In this paper, composite scaffolds of op-HA with controlled grafting different amounts of LAc oligomer (1.1, 5.2, and 9.1 wt %) were fabricated and implanted to repair rabbit radius defects. The dispersion of op-HA nanoparticles was more uniform than n-HA in chloroform and nanocomposites scaffold. Calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Our results agree with those of other previously published studies, where they even observed the formation of new cortex and recanalisation of the marrow cavity via inspection [15].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results agree with those of other previously published studies, where they even observed the formation of new cortex and recanalisation of the marrow cavity via inspection [15].…”
Section: Discussionsupporting
confidence: 94%
“…In particular, the broad absorbance band at 1031-1042 cm −1 corresponding to the (υ 3 ) asymmetric vibration lines of (PO 4 ) 3− group indicates an amorphous Ca-P structure [34]. Moreover, the study of the HA surface chemical composition by means of X-ray photoelectron spectroscopy ( Figure 7) enables identification of the typical chemical states of the components in Polymers 2017, 9, 410 8 of 15 an ideal hydroxyapatite surface. Also, the estimated Ca/P ratio of 1.34 (see Table 1 with the atomic composition percentages) is in good agreement with other quasi-stoichiometric HA structures obtained by magnetron sputtering techniques in an inert atmosphere [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3338 Grafting organic molecules to the surface of ceramic nanoparticles enhances their dispersion in organic polymers as well as interfacial binding between the polymer and ceramic phases, resulting in improved mechanical properties and stimulation of cell attachment, proliferation, and differentiation. 37,3945 However, the effects of surface grafting on mechanical and biological properties of reactive and settable nHA/polymer composite cements have not been investigated. Furthermore, studies investigating grafting of polyisocyanates to nHA have utilized solvents such as dimethyl formamide (DMF), which are cytotoxic and not suitable for injectable biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The new bone formation was guided by the scaffold of g-HA/PLGA. There were few fibrous tissues at the interface of the implant and new bones compared to the cell-free scaffold of g-HA/PLGA, which was reported by Wang et al (2016).…”
Section: Histological Analysismentioning
confidence: 60%